(untitled) (Beacon: International Journal of Education and Social Studies, 2025)
Digital transformation has become a strategic necessity for higher education institutions seeking to enhance educational quality, operational efficiency, and institutional competitiveness. This study aims to examine the effects of digital transformation adoption determinants on personnel competencies in Indonesian higher education institutions. A mixed-methods approach with an explanatory sequential design was employed. Quantitative data were collected from 420 respondents representing public and private higher education institutions across Indonesia, while qualitative data were obtained through in-depth interviews with key stakeholders. Data were analyzed using Structural Equation Modeling (SEM) and thematic analysis. The findings reveal that organizational culture, organizational structure, and artificial intelligence (AI) adoption have positive and significant effects on digital transformation adoption. Furthermore, organizational culture, organizational structure, AI adoption, and digital transformation adoption positively influence personnel competencies. Digital transformation adoption was identified as the strongest predictor of personnel competency development and serves as a mediating variable between organizational factors and personnel competencies. Based on the empirical findings, this study proposes the Digital Transformation Adoption and Personnel Competency (DTAPC) Model, which provides a strategic framework for supporting workforce development and successful digital transformation initiatives in Indonesian higher education institutions. The study contributes to the growing literature on digital transformation by highlighting the importance of organizational and technological factors in enhancing human resource competencies in the higher education sector.